(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background Recent evidence is known that functional foods are foods that provide the latest prospects for preventing nutritional problems not only because of their macro and micro nutrient content but their bioactive components that have an effect on the methylation process at the cellular level. Objective: the purpose of this study was to determine the consumption of functional foods based on local foods in pregnant women in Makassar City Method: A cross sectional study design. The sample size was 647 pregnant women taken from 41 Puskesmas in Makassar City, except the Sangarrang Kepulauan Puskesmas. Functional food intake was collected using the FFQ method, Macro and micro nutrient intake with Food recall 2 x 24 hours. The data collection enumerators were 21 graduates from Nutrition III / IV graduates. Enumerators are trained for two days. Results; showed that functional foods consumed by pregnant women based on local foods are sources of fiber, probiotics, Vitamin C, carotenoids, omega 3/9 and folifenol respectively (39.03 ± 36.78), (21.15 ± 7.74), (38.44 ± 30.9), (90.04 ± 50.53), (83.42 ± 60.42) and 166.57 ± 92.66). Conclusion; is that consumption of functional foods based on local foods in pregnant women is good.